P-71 BARIATRIC SURGERY AND THE IMPACT ON THE LIVER. COHORT STUDY OF ONE CENTER IN ARGENTINA - Maria Mercedes Cortese; Lucas Muñoz; Gabriel Rifrani; Natalia Ahumada; Daiana Arnedillo; Antonella Cordone; Morena Carvalho; Martina Rigoni; Alceo Galimberti; Norberto Tamagnone; Federico Tanno; Hugo Tanno; et al. (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Losing weight and lifestyle modifications are still pillars of treatment for metabolic associated steatotic liver disease (MASLD) and steatohepatitis (MASH), despite the emerging therapies. Bariatric surgery (BS) has been reported to improve degeneration, inflammation, and fibrosis. Aim: To describe liver histological patterns and biochemical parameters in patients undergoing BS. Patients / Materials and Methods: Observational retrospective study including 93 patients who underwent BS in one center in Argentina, between 2017-2023. A liver biopsy (LB) was performed during the surgery to all patients. Anthropometric and biochemical parameters, including fibrosis-4 index (FIB-4), were assessed intraoperatively and 6 months after surgery. Results and Discussion: The mean age was 44.1 (±9.4), women 92.5%. Mean BMI before surgery, 42.7 (±7.1) kg/m2. We studied 25 patients who presented type II diabetes mellitus and 72 who were insulin resistance (77.4%). Other comorbidities like high blood pressure and hypothyroidism were found in 43% and 25.8% of this sample. LB showed MASLD in 63.4%, and MASH in 25.8% of cases. Liver fibrosis was present in 65% of patients, being significant (≥F2) in only 14 patients (15.3%) (F2: 10, F3: 3, F4: 1;). Strikingly, FIB-4 <1.3 was observed in 10/14 (71%) patients with fibrosis stage ≥F2. Patients with significant fibrosis had lower platelets and higher glycemia, AST, triglycerides, HOMA and FIB-4 compared with those who did not present these disorders (p<0.05). Six months after surgery, a reduction of BMI was observed compared to the preoperative BMI (42.7 vs 39.4 kg/m2; p=0.034). After six month of surgery, also a significant improvement of AST, glycemia, triglycerides and HOMA were shown in patients with significant fibrosis (p<0.05). Conclusions: Despite the high prevalence of MASLD in this cohort, significant fibrosis was found in only 15%. FIB-4 was not effective to predict liver fibrosis ≥F2. Bariatric surgery can induce long-term improvement of cardiometabolic risk factors.